2016
DOI: 10.1556/038.51.2016.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Synthetic Feeding Attractant Increases Catches of Rhagoletis batava Hering and Carpomyia schineri Loew. in Fluorescent Yellow Sticky Traps

Abstract: The addition of the synthetic Rhagoletis feeding attractant (consisting of ammonium carbonate and ammonium acetate, developed previously for Rhagoletis cerasi L.) to both fluorescent yellow or transparent sticky traps significantly increased catches of the fruit flies Rhagoletis batava Hering (pest of sea buckthorn) and Carpomyia schineri Loew. (pest of rose hips). Traps with lures were detecting the occurrence of both species 1-2 weeks before as compared to traps without lure, and quantitative aspects of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
(9 reference statements)
1
7
0
Order By: Relevance
“…Flight peak was reached between the middle of July and middle of August in the Lithuanian population. Such annual fluctuations of flight period were most likely caused by the differences in the weather conditions.The total duration of R. batava flight period established in the present study, is close to that recorded in Germany(Toth et al, 2016) and differs from that reported in Mongolia and Russia (Siberia, Asian part), where flight period starts 2-3 weeks earlier(Shamanskaya, 2015;Zhao et al, 2017).…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Flight peak was reached between the middle of July and middle of August in the Lithuanian population. Such annual fluctuations of flight period were most likely caused by the differences in the weather conditions.The total duration of R. batava flight period established in the present study, is close to that recorded in Germany(Toth et al, 2016) and differs from that reported in Mongolia and Russia (Siberia, Asian part), where flight period starts 2-3 weeks earlier(Shamanskaya, 2015;Zhao et al, 2017).…”
supporting
confidence: 72%
“…As special traps are commonly used for insect pest monitoring, the data on trap type (including colour) suitable for R. batava trapping are needed. Although flies of many species from genus Rhagoletis were attracted by yellow colour (Agee et al, 1982; Yee, 2011; 2012; 2013; Yee, Goughnour, 2011; Toth et al, 2014), this was not the case for R. batava, when field testing was carried out using sticky "cloak" (PAL and PALz) type traps (Toth et al, 2016). It still remains to be investigated whether this behavioural phenomenon of R. batava species is an exception within the genus Rhagoletis.…”
Section: Introductionmentioning
confidence: 99%
“…Lures contained 5 g of AC, AA, or 5 g of a 1:1 mix, except in one test where 10 g of a 1:1 mix was used. The 1:1 mix of AC:AA is the ratio in a commercial lure developed for R. cerasi ( Toth et al 2016 ). Ammonia release rate was regulated by varying hole diameters, and determined from the AC lure by measuring weight loss as well as using Nessler’s reagent following methods of Rana and Mastrorilli (1998) ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The choice of attractant for R. cerasi has been ammonium acetate (AA; Katsoyannos et al 2000 , Molet and Moylett 2016 ) or a mix of it and AC ( Toth et al 2016 ). This raises the question of whether AA can be as or more efficacious for R .…”
mentioning
confidence: 99%
“…Current tools available for monitoring R. batava populations are ineffective. Yellow sticky traps are still recommended and used [11] and the use of nonspecific attractant has also been recently reported [12]. Pheromone identification could fill this gap and be applied for pest population monitoring and potentially contribute to environmentally friendly pest control.…”
Section: Introductionmentioning
confidence: 99%